2014
DOI: 10.1038/ncomms4893
|View full text |Cite
|
Sign up to set email alerts
|

Cascading ecological effects of eliminating fishery discards

Abstract: Discarding by fisheries is perceived as contrary to responsible harvesting. Legislation seeking to end the practice is being introduced in many jurisdictions. However, discarded fish are food for a range of scavenging species; so, ending discarding may have ecological consequences. Here we investigate the sensitivity of ecological effects to discarding policies using an ecosystem model of the North Sea—a region where 30–40% of trawled fish catch is currently discarded. We show that landing the entire catch whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 39 publications
3
66
0
4
Order By: Relevance
“…Another study on the effect of landing discards and improving selectivity in the North Sea using an ecosystem model showed that landing discards had negative impacts on seabirds and mammals (Heath et al 2014), a finding which is consistent with those of the present study. Heat et al (2014) did, however, observe that seabirds and mammals could benefit from improved selectivity (depending on fishing pressure), which was not the case for the seabirds in the present study, though some of the mammals (e.g.…”
Section: Ecological Effectssupporting
confidence: 83%
See 2 more Smart Citations
“…Another study on the effect of landing discards and improving selectivity in the North Sea using an ecosystem model showed that landing discards had negative impacts on seabirds and mammals (Heath et al 2014), a finding which is consistent with those of the present study. Heat et al (2014) did, however, observe that seabirds and mammals could benefit from improved selectivity (depending on fishing pressure), which was not the case for the seabirds in the present study, though some of the mammals (e.g.…”
Section: Ecological Effectssupporting
confidence: 83%
“…It also had little effect on the landings and profit, as the biomass of the discarded fish is low, even though their numbers are high. Another study on the effect of discards in the North Sea showed that landing discards had no effect on the stock size of fish groups (Heath et al 2014).…”
Section: Effects Of Discarding On Commercial Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adopted feeding plan was favorable because it largely reflected the feeding habits of gurnard in the local environment. Many studies have shown that fishery discards, which are not targeted by the http://epublishing.ekt.gr | e-Publisher: EKT | Downloaded at 10/05/2018 11:11:11 | fishery, may affect the biodiversity of the marine ecosystem (Johnsen & Eliasen, 2011;Heath et al, 2014;Sardà et al, 2015). When the current study was granted, the new EU CFP had not yet come into force; however, this study confirms that local fish species that are excluded by the market contain high amounts of protein and n-3-rich fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…58 Food subsidies to wildlife as a result of human activity have an important effect on terrestrial and aquatic ecosystems, and intentional discarding at sea is recognized as one of the major global subsidies. Heath et al (2014). 59 Wilson and Jacobsen (2009), p. 6.…”
mentioning
confidence: 99%